There Was an Old Lady Who Swallowed a Fly - Taback, Simms (New York : Viking, 1997)
Based on "There was an old lady who swallowed a fly," this book gives young readers an eye-popping version of the well-loved poem.
Keywords: Folk songs, English -- Texts; Folk songs; Nonsense verses; Toy and movable books; Picture book